Extraction of titanium from low-grade ore with different leaching agents in autoclave - Rodriguez, Mario Humberto (2020)
The progressive depletion of primary sources to obtain metals has led to the search for alternative sources for their recovery. In the particular case of titanium, titaniferous sands are a viable option for obtaining this metal. This paper presents the results of the dissolution of titanium from titaniferous sands of Buenos Aires province (Argentina) in a laboratory autoclave (450 mL of capacity). The operating parameters studied were as follows: different acids (HF, H2SO4 and mixtures of these acids); leaching agent concentration, 5–20% v/v; temperature, 75–150 ◦C; time, 30–180 min; solid–liquid ratio, 0.9–3.6% w/v; stirring speed, 110–550 rpm. The obtained results indicate that the increase in the leaching agent(s) concentration, temperature and time of contact with the acid mixtures have a marked effect on the dissolution reaction of titanium. Optimal conditions to achieve 89% extraction of titanium were obtained by leaching at 123 ◦C, 330 rpm, 80 min and 1.8% w/v with a mixture of 15% HF (v/v) and 10% H2SO4 (v/v).